Soil Microclimate and Persistence of Foodborne Pathogens Escherichia coli O157:H7, Listeria monocytogenes, and Salmonella enterica Newport in Soil Affected by Mulch Type - Shirley A. Micallef; Mary Theresa Callahan; Rachel McEgan; Louisa Martinez (Journal of Food Protection, 2023)
Mulching is a common agricultural practice that benefits crop production through soil moisture retention, weed suppression, and soil temperature regulation. However, little is known about the effect of mulch on foodborne pathogens present in soil. In this study, the influence of polyethylene plastic, biodegradable corn-based plastic, paper, and straw mulches on Escherichia coli O157:H7, Listeria monocytogenes, and Salmonella enterica Newport populations in soil was investigated. Silt loam soil in troughs was inoculated with a cocktail of the pathogens and covered with mulch or left bare, then incubated for 21 days, during which bacteria were enumerated and environmental parameters monitored. Bacterial counts declined in all treatments over time (p < 0.001) but persisted at 21 days at 0.8–0.95 log CFU/g. Pathogens also declined as a factor of mulch cover (p < 0.01). An exponential decay with asymptote model fit to the data revealed slower rates of decline in soil under mulches for all pathogens (p < 0.05) relative to bare soil. Compared to the average for all treatments, rates of decay in bare soil were 0.60 (p < 0.001), 0.45 (p < 0.05), and 0.63 (p < 0.001) log CFU/g/d for E. coli O157:H7, L. monocytogenes, and Salmonella, respectively. Linear multiple regression revealed that soil hydrological parameters were positively correlated (p < 0.05) with bacterial counts, while day soil temperatures were negatively correlated (p < 0.001), suggesting that higher day temperatures and lower moisture content of bare soil contributed to the faster decline of pathogens compared to mulched soil. A microcosm experiment using field soil from lettuce cultivation suggested no influence of prior mulch treatment on pathogens. In summary, pathogen decline in soil was modified by the soil microclimate created under mulch covers, but the effect appeared was restricted to the time of soil cover. Slower decline rates of pathogens in mulched soil may pose a risk for contamination of fresh market produce crops.